Pemasaran Konten: Menyusun Narasi Menarik untuk Melibatkan Audiens dan Mempromosikan Batik Tradisional Lampung - Carolina, Thabita (Business Perspective Journal, 2024)
This study aims to explore the application of content marketing in promoting Lampung Batik through social media, specifically Instagram, with a focus on crafting engaging narratives to enhance audience engagement. The background of this research stems from the growing use of social media as a marketing tool, yet limited studies have examined effective strategies for constructing marketing narratives for local cultural products such as Lampung Batik. The method employed in this research is content analysis with a qualitative approach, where data was collected through observation of marketing content from several Instagram accounts promoting Lampung Batik. The findings indicate that effective marketing narratives are built through captivating visuals, storytelling about the batik-making process, the use of relevant hashtags, customer testimonials, and collaborations with influencers to expand audience reach. In conclusion, narratives that are consistently and authentically constructed can introduce Lampung Batik as a highly valuable cultural product, as well as increase audience awareness of its existence and the importance of preserving this traditional batik. Recommendations for future research include developing marketing strategies on other social media platforms and strengthening collaborations with the cultural and tourism sectors to broaden the audience. Keywords: content marketing, batik lampung, marketing narrative, instagram